Appearance of New Oscillation (Named Oscillation H) Induced by Na2SO4 and K2SO4 in Electroreduction of H2O2 on Platinum. Issue 2 (2nd December 2016) - Mukouyama, Yoshiharu; Kawasaki, Hirokazu; Hara, Daisuke; Yamada, Yuri; Nakanishi, Shuji
Abstract : The reduction of H2 O2 on Pt electrodes in H2 SO4 solutions shows a various types of electrochemical oscillations, named sequentially from A to G, as has been reported previously. This paper shows that salts such as Na2 SO4 and K2 SO4, which are often used as supporting electrolytes for electrochemical reactions, cause significant effects on the H2 O2 reduction. A new potential oscillation, named oscillations H, appears in the H2 O2 -H2 SO4 -Pt system when Na2 SO4 or K2 SO4 is added to the solutions. Oscillation H is induced by the cations originating from the salts, Na + and K +, though they do not react on Pt electrode. In the presence of Na + or K +, the local pH at the electrode surface becomes basic, and consequently the oxidation of HO2 −, formed via a dissociation of H2 O2 (H2 O2 → HO2 − + H + ), occurs on the electrode surface. Oxygen bubbles due to the HO2 − oxidation evolve from the electrode synchronously with the potential oscillation. Detailed studies, including electrochemical impedance measurements and numerical simulation, reveal that oscillation H can be explained by an interplay of the HO2 − oxidation and an autocatalytic effect involved in the H2 O2 reduction.